Systematic Literature Review (SLR): Peran Sumber Daya Manusia terhadap Kualitas Pelayanan pada Industri Food And Beverage (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The food and beverage (FnB) industry is one of the main supporting sectors of tourism in Indonesia and has experienced rapid growth along with the increasing number of tourist activities and consumer demand. However, previous studies indicate that Service Quality in the FnB industry remains suboptimal, particularly in aspects related to human resources (HR). Issues such as inconsistent service performance, low responsiveness, and limited employee competence and work attitude are commonly identified. This study aims to systematically examine the role of human resources in Service Quality within the FnB industry and to identify key factors, management strategies, and existing research gaps. This research employed a Systematic Literature Review (SLR) method using the PICOC framework, analyzing 20 national and international journal articles published between 2015 - 2025 and retrieved from Google Scholar. The findings reveal that the most influential HR factors affecting Service Quality include competence, communication skills, work attitude, experience, and employee training. Furthermore, effective human resource management practices demonstrate a positive relationship with improved Service Quality. Nevertheless, the review identifies a lack of comprehensive studies integrating HR management and Service Quality within the specific Context of the Indonesian FnB industry, indicating opportunities for future research.